Variations in the frenal morphology in the diverse population: A clinical study - Vikas Jindal; Rupinder Kaur; Amit Goel; Atika Mahajan; Neha Mahajan; Atin Mahajan (Wolters Kluwer Medknow Publications, 2016)
Background: The upper labial frenum is a normal anatomic structure with inherent morphological variations. Frenum has variations depending upon the attachment of fibers along with the presence of structural variations. Aim: The aim of this study was to evaluate the prevalence of frenal variations in a diverse ethnic population of Sundernagar, Himachal Pradesh. Materials and Methods: This study was conducted on 500 subjects within age group of 16-40 years (285 females, 215 males). Intraoral examination was done to evaluate the variations in frenum and photographs were taken. Results: In this study, depending upon structural variations, normal frenum was most common followed by frenum with nodule while frenum with appendix was found to be least common. However, no significant difference was found between males and females (P > 0.05) with respect to all frenal attachments. Furthermore, other structural variations were found in the diverse population of Sundernagar, Himachal Pradesh. Conclusion: Upper labial frenum is a small anatomical landmark in the oral cavity found to have diverse morphology. The dentist needs to give due importance for frenum assessment during the oral examination.